Pengaruh Penambahan Serat Pohon Bambu Ampel (Bambusa Vulgaris) pada Komposit Hybrid untuk Material Bumper Kendaraan Bermotor - Gito Mulyo Inggit Bagus Satria; Sri Hastuti; Ikhwan Taufik (Pusat Riset dan Inovasi Nasional, 2024)
Technological developments continue to increase in line with the times, producing various innovations that provide benefits to society, especially in the material sector. The use of a mixture of natural and synthetic fibers in composites (hybrid) has produced a stronger material, which can function as an alternative material for car bumpers. This research was carried out with the aim of determining the values ​​of impact toughness, tensile strength, and failure patterns that occur in the fracture cross section of the specimen through macro photographs. In this research, a hybrid composite was formed by combining ampelous bamboo fiber, fiberglass, and polyester resin. Variations in volume fraction applied include: 5%:25%:70%, 10%:25%:65%, and 15%:25%:60%. The specimens were formed according to ASTM E23 standards for impact tests and ASTM D638 for tensile tests. The results of the impact and tensile tests showed that the lowest value of impact toughness was 0.0744 J/mm² and tensile stress was 120.29 MPa. Meanwhile, the highest value for impact toughness was 0.0986 J/mm² and the tensile stress value was 147.65 MPa. Macro photo analysis of the fracture cross section is categorized as splitting in multiple areas and the fracture cross section also shows debonding and fiber pull out after the fracture occurred.